IDENTIFIKASI FLUKS MAGNETIK DARI GERAK PASANGAN BINTIK BIPOLAR - Clara Y. Yatini (Jurnal Sains Dirgantara, 2005)
Proper motion of a pair of bipolar spots is analyzed using TRACE white light data to find their relation with the emerging flux. These spots were located under flaring region of NOAA 0424, which ejected an M1.7/S N flare on August 5, 2003. As the result, it is found that the preceding moved westward of the following. We interpret this as the indicator of emerging magnetic flux triggering flare.